Researching Translanguaging as a Feasible Pedagogical Practice: Evidence from Chinese English-as-a-Foreign-Language Students' Perceptions. (August 2022) - Jiang, Zhihui Will; Zhang, Lawrence Jun; Mohamed, Naashia
Translanguaging as pedagogical practice and a theory of language has gained increasing importance in recent years. However, little research has reported Chinese English-as-a-foreign-language students' perceptions of translanguaging; neither has research examined the predictive effects of the factors contributing to the amount of student translanguaging in the Chinese English-as-a-foreign-language classrooms. This study intended to fill the gap by inviting 292 Chinese English-as-a-foreign-language students to respond to a questionnaire that explores students' perception of translanguaging. Two research questions were addressed: first, how do students' attitudes to translanguaging vary across second-language proficiency? Second, how is the amount of student translanguaging predicted by students' attitudes to translanguaging and the amount of teacher translanguaging? The results of a one-way analysis of variance revealed a statistically significant difference among the four groups in attitudes to teacher translanguaging and students' translanguaging. A post hoc test found that non-English major first-year university students had a significantly higher level of acceptance of teachers' and students' translanguaging than English major first-year university students. Multiple regression analysis showed that the amount of teacher translanguaging and student attitudes to translanguaging explained a significant quantity of the variance in the amount of student translanguaging. The implications of the study were also discussed.